2003
DOI: 10.1053/jhep.2003.50218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ribavirin on hepatitis C viral kinetics in patients treated with pegylated interferon

Abstract: A dynamic equilibrium between viral production and clearance characterizes untreated chronic hepatitis C viral infection. After initiating antiviral treatment, a typical multiphasic decay of viremia can be observed and analyzed using mathematical models. To elucidate the antiviral mechanism of ribavirin when used in combination with (pegylated) interferon alfa, we investigated kinetic parameters in patients with chronic hepatitis C treated with either peginterferon ␣-2a with or without ribavirin and standard i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
285
3
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(322 citation statements)
references
References 27 publications
23
285
3
8
Order By: Relevance
“…The study was designed to explore the effect of telaprevir in combination with peginterferon on HCV kinetics, and the safety and pharmacokinetics of this combination. The median change in HCV RNA from baseline to day 15 in patients who received placebo and peginterferon alfa-2a was Ϫ1.09 log 10 ; this result is consistent with other studies of interferon monotherapy in patients with genotype 1 hepatitis C. 6,7,11 As in the prior phase 1b study, 4 telaprevir demonstrated substantial antiviral activity: in the 8 patients who received telaprevir alone, the median change from baseline to day 15 was Ϫ3.99 log 10 , and 1 patient achieved undetectable HCV RNA levels. The median change from baseline in HCV RNA of Ϫ5.5 log 10 in the telaprevir and peginterferon alfa-2a group and the undetectable HCV RNA levels in 4 patients in this group confirmed the hypothesis that telaprevir in combination with peginterferon would result in a greater antiviral effect than telaprevir alone.…”
Section: Discussionsupporting
confidence: 88%
“…The study was designed to explore the effect of telaprevir in combination with peginterferon on HCV kinetics, and the safety and pharmacokinetics of this combination. The median change in HCV RNA from baseline to day 15 in patients who received placebo and peginterferon alfa-2a was Ϫ1.09 log 10 ; this result is consistent with other studies of interferon monotherapy in patients with genotype 1 hepatitis C. 6,7,11 As in the prior phase 1b study, 4 telaprevir demonstrated substantial antiviral activity: in the 8 patients who received telaprevir alone, the median change from baseline to day 15 was Ϫ3.99 log 10 , and 1 patient achieved undetectable HCV RNA levels. The median change from baseline in HCV RNA of Ϫ5.5 log 10 in the telaprevir and peginterferon alfa-2a group and the undetectable HCV RNA levels in 4 patients in this group confirmed the hypothesis that telaprevir in combination with peginterferon would result in a greater antiviral effect than telaprevir alone.…”
Section: Discussionsupporting
confidence: 88%
“…23,24 Similarly, declines ranging from 0.86 log 10 to 1.08 log 10 have been reported for HCV patients injected once with 180 g pegylated IFN-␣-2a. 24,25 Therefore, comparison of immune and antiviral activities induced by CPG 10101 and IFN suggests that CPG 10101 may provide similar antiviral effects and modulation of the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]23,25,26 Here, viral kinetics in 20 patients with chronic hepatitis C and persistently normal ALT levels and 19 patients with elevated ALT levels were analyzed. The first-phase decline of the viral load is mainly determined by the clearance rate of free viral particles c and the effectiveness of blocking virus production ⑀.…”
Section: Discussionmentioning
confidence: 99%
“…Viral Kinetic Model. Viral kinetics were calculated according to the kinetic model described by Herrmann et al 15 Compartments were used for the free viral load, productively infected, and uninfected hepatocytes. Constant rates were assumed for clearance of free virus (c), infected cell loss (␦), virus production, and de novo infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation